(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article explores the role of modern innovative pedagogical technologies in enhancing students’ critical and creative thinking skills within higher education. The study applies a comprehensive experimental approach, integrating problem-based learning, project-based learning, and digital interactive tools. The findings demonstrate that these methods significantly improve students’ analytical thinking, independent decision-making, and ability to generate original solutions. Additionally, the use of innovative technologies contributes to increased student engagement and learning motivation. The results highlight the importance of integrating active and technology-driven approaches into contemporary educational practices to foster higher-order thinking skills.